2000
DOI: 10.1289/ehp.00108961
|View full text |Cite
|
Sign up to set email alerts
|

The question of declining sperm density revisited: an analysis of 101 studies published 1934-1996.

Abstract: In 1992 Carlsen et al. reported a significant global decline in sperm density between 1938 and 1990 [Evidence for Decreasing Quality of Semen during Last 50 Years. Br Med J 305:609-613 (1992)]. We subsequently published a reanalysis of the studies included by Carlsen et al. [Swan et al. Have Sperm Densities Declined? A Reanalysis of Global Trend Data. Environ Health Perspect 105:1228-1232 (1997)]. In that analysis we found significant declines in sperm density in the United States and Europe/Australia after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
262
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(282 citation statements)
references
References 75 publications
12
262
1
7
Order By: Relevance
“…However, there is a strong belief that the decrease in fertility can be directly related to the paralleled increase in obesity. In support of this theory, Swan et al revealed that sperm counts have continued to decrease between 1934 and 1996 by as much as 1.5% annually in the USA as well as other parts of the Western world with such decrease not observed in regions where obesity is less prevalent [13].…”
Section: Introductionmentioning
confidence: 98%
“…However, there is a strong belief that the decrease in fertility can be directly related to the paralleled increase in obesity. In support of this theory, Swan et al revealed that sperm counts have continued to decrease between 1934 and 1996 by as much as 1.5% annually in the USA as well as other parts of the Western world with such decrease not observed in regions where obesity is less prevalent [13].…”
Section: Introductionmentioning
confidence: 98%
“…These so-called endocrine disruptors, endocrine modulators or hormone-mimetic substances have been associated with a decrease in sperm counts in man (Swan et al 2000), increased frequencies of sex-hormone dependent cancers (breast, testis, prostate, etc. ), genital abnormalities, premature puberty in females, and increased occurence of endometriosis in humans (Gist 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s various manmade chemicals were also identified as disrupters of the endocrine system [10,11] and their fate and behavior became a major research topic [12]. Since then, accumulating evidence suggests that these chemicals may also affect the health and possibly the fertility of humans and wildlife [13,14,15].…”
Section: Introductionmentioning
confidence: 99%